Relationship Between Group Learning and Interpersonal Skills With Emphasis on the Role of Mediating Emotional Intelligence Among High School Students. (June 2018) - Moradi, Saeid; Faghiharam, Batoul; Ghasempour, Kobra
The purpose of this study was to investigate the relationship between group learning and interpersonal skills, with emphasis on the mediating role of emotional intelligence among high school students in Tehran. This research is a descriptive correlation type that was implemented using structural equation modeling method. The statistical population of this study includes 1, 800 high school students. The sample was 316 subjects, using simple random sampling and Cochran formula. The data-gathering tools in this research were Matson's Interpersonal Communication Skills Questionnaire, Bradberry-Greave's Emotional Intelligence Questionnaire, and Lauren-Nemeth's Group Learning Questionnaire with a reliability of 0.81, 0.87, and 0.71, respectively, achieved. For data analysis, structural equation modeling and PLS software were used. The research results indicate that group learning also directly affects interpersonal skills and emotional intelligence and indirectly affects interpersonal skills through emotional intelligence.